(untitled) (American Journal of Pedagogical and Educational Research, 2023)
This article deals with the genre of “Sichjo” that originated in Korea during the Joseon (Li) Literature period (1392-1910). This genre is considered a lyrical genre with a certain image of excitement and experience, which embodies the traditions of Korean folklore and the three religious-philosophical teachings of the peoples of the Far East (Confucianism, Buddhism and Taoism).